Imaging and classifications of atlantoaxial dislocation: a narrative review - Guangzhou Li; Hao Zhang; Qing Wang (EFORT Open Reviews, 2025)
Radiography is of importance in the diagnosis of atlantoaxial dislocation (AAD), and it is the basic imaging technique. However, it should not be the sole diagnostic modality, especially in complex or unclear cases. Conventional X-ray includes an open-mouth odontoid view and a cross-table lateral view, and careful study of radiological findings is crucial to give an early diagnosis of AAD. Lateral flexion-extension dynamic views are only used as an additional supplement in some special cases. Although X-ray images are enough to diagnose AAD in most cases, some patients suspected with AAD should be evaluated with the readily available and quick CT scan. If patients with AAD have symptoms of spinal cord and medullary compression, apart from conventional radiographs, a combination of high-quality CT and MRI of cervical spine are necessary for the diagnosis and choice of treatment. For patients with AAD, both the thin slice CT scanning with coronal, sagittal and three-dimensional reconstruction images and MRI of cervical spine are fundamental to surgical planning. Clinical classifications of AAD associated with imaging are useful in determining treatment strategies. The present study reviews publications on imaging and clinical classification of AAD to aid the clinician in the evaluation and management of these dislocations.